The Discharge Choreography: A Narrative Review of Team-Based Workflows to Prevent Post-Hospitalization Complications - Ghobri, Samira Ahmed Ismail; Byan Hussein Aref; Amani Mohammed Ali Arishi; Reem Mohammed Ahmed Shaabi; Azah Abdullah Hassan Masrahi; Samira Ali Hussin Halawi; Mashaer Mohammed A Mahdi; Walaa Abdu Khardali; Rehab Mohammed Abdaly; Yosra Mousa A Farhan; et al. (Saudi Journal of Medicine and Public Health, 2024)
Background: Hospital discharge is a high-risk transition of care, often characterized by fragmented communication, unresolved clinical issues, and inadequate patient preparation. Poorly executed discharges are a primary driver of preventable hospital readmissions, adverse drug events, and patient harm. Traditional models, which place the overwhelming burden on a single nurse or physician, are prone to error and system failure, as they inadequately address the multifaceted clinical, administrative, and social needs of the departing patient. Aim: This narrative review aims to synthesize current evidence to propose and define a "Discharge Choreography" model to ensure a seamless, safe, and patient-centered transition from hospital to home or next care setting. Methods: A systematic search was conducted across PubMed, CINAHL, Scopus, and Web of Science for literature published between 2010 and 2024. Results: The review identifies four critical, interdependent domains of the discharge process. Evidence confirms that structured workflows leveraging all team members improve medication adherence, follow-up attendance, and patient comprehension while reducing readmission rates by 10-30%. Key barriers include role ambiguity, insufficient training for support staff, and lack of integrated health information technology. Conclusion: Discharge must be reconceptualized from a solitary clinical task to a choreographed operational process. The proposed model provides a blueprint for health systems to deliberately allocate discharge responsibilities across licensed and non-licensed team members, creating a reliable, redundant safety net that protects patients during this vulnerable period and improves health system performance.